Mechanical Cardiopulmonary Resuscitation (CPR) Is Better Than Manual CPR? Literature Study - Wijaya, Sapondra; Susmini, Susmini; Soewito, Bambang; Wibowo, Wahyu Dwi Ari (Universitas Muhammadiyah Lamongan, 2024)
Introduction: Mechanical CPR mitigate rescuer fatigue and ensure adherence to guidelines, potentially enhancing overall survival rates. Contrarily, manual CPR relies on human skill, presenting challenges in maintaining uniformity and endurance. Unveiling the complexities within this juxtaposition becomes imperative in shaping future resuscitative paradigms. The purposeof studi is to determine the effectiveness of mechanical CPR in cardiac arrest management compared to manual CPRMethods: Database used were Pubmed and Proquest using the keywords